Sedulur Papat Limo Pancer as a Concept of Javanese Emotional Intelligence - Devietha Kurnia Sari; Darmawan Muttaqin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Javanese have various philosophies as a guideline to achieving perfection in life. One of them is Sedulur Papat Limo Pancer. This philosophy guides for a human to appreciate and control their emotions along with their activities or dealing with daily problems. Sedulur Papat represents the four human emotions or desires consisting of amarah (anger), lawwamah (greed/gluttony), supiah (lust), and mutmainnah (sloth). Limo Pancer represents man himself as the controller of his four emotions. This article aims to discuss Sedulur Papat Limo Pancer as a concept of Javanese's emotional intelligence. By comparing with the concept of emotional intelligence in Psychology, the concept of Sedulur Papat Limo Pancer explains more detail in the emotions domain that needs to be controlled. However, the concept of emotional intelligence explains more detail about the aspects of emotional intelligence compared to the concept of Sedulur Papat Limo Pancer. The integration between the Sedulur Papat Limo Pancer with the emotional intelligence concept can be used to understand emotional intelligence comprehensively.